On exact irreducible representations of locally normal groups - Tushev, A. V. (Ukrains’kyi Matematychnyi Zhurnal, 1993)
We obtain a generalization of the Gaschutz criterion of existence of exact irreducible representations of finite groups to the class of normal groups.